PENDAMPINGAN PENGELOLAAN DAN PELAPORAN PADA KOPERASI KPRI RUKUN KENDAL - Tri Novita Wahyuni; Dendy Kurniawan (Jurnal Padamu Negeri, 2024)
One of the main problems faced in the management of cooperatives in Indonesia today is the level of competence of human resources within the cooperative, and the level of financial competence in the sustainability of cooperatives is one of the few parts of human resource competence in cooperative development that needs to be considered. Theoretical and practical understanding of cooperative managers regarding the recording and reporting of cooperative finances in accordance with accounting standards is carried out in this community service. The method used is called Participatory Action Research, and involves eight steps. Feedback from the community shows that after a period of intensive outreach by the community outreach team, KPRI Rukun Kendal can conduct consultations and business exchanges in accordance with the Micro, Small, and Medium Enterprise Exchange Standards. The assistance provided by the community service team to the KPRI Rukun Kendal cooperative managers is ongoing. Although community service activities have been completed, the evaluation and follow-up of the evaluation results